If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37(8x + -23) = 37 Reorder the terms: 37(-23 + 8x) = 37 (-23 * 37 + 8x * 37) = 37 (-851 + 296x) = 37 Solving -851 + 296x = 37 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '851' to each side of the equation. -851 + 851 + 296x = 37 + 851 Combine like terms: -851 + 851 = 0 0 + 296x = 37 + 851 296x = 37 + 851 Combine like terms: 37 + 851 = 888 296x = 888 Divide each side by '296'. x = 3 Simplifying x = 3
| F(x)=60+10 | | 5+5x=7x+5 | | 3b+2=b+10 | | 4w+8y+3x+9x-13y+4w= | | 2x-2(x+11)=5x | | y=3x^2+16x-8 | | 4w+9x+11y+3w+3x-6y= | | 5p+7=4p+3 | | 5h-4=-16 | | x+3(x-1)=4 | | 9+2.71t=-4.8t-6 | | -x^2-2x-8=0 | | 24-x=18 | | -x^2-7x+22=0 | | M^2+7M=4 | | 2(x+3y-1)=y | | 5(x-y)+2y=-26 | | 7x-(3x-4)=8-6x-6+5x | | log(7)=2 | | 14.40+4.05p=4.50(3+p) | | y=13x+404+46 | | 3(3x-6)=1-2x | | x+(x-10)+2(x-10)+6=100 | | 3x^2-5xy+2y^2+3x=0 | | 2.8-5.6= | | 5y-30y+10=-52+2y-4y | | (x^2+x)-6= | | 5*24-3x=90 | | 3k-s=7k-21 | | 5(y+2)=4-7 | | =y-6y^3 | | -(x-1)-3(x+4)=x |